Under a rock - Stein, Chris 1950- (St. Martin's Press, 2024)
"Debbie Harry defined iconic band Blondie's look. Chris Stein--her performing partner, lover, and lifelong friend--was its architect and defined its sound. "Parallel Lines", their third album, catapulted to #1, sold 20 million copies, and launched singles like "Heart of Glass", "Rapture," and "One Way or Another", providing the beat when Bianca Jagger and Halston danced at Studio 54 and the soundtrack to every 1970's punk-soundtracked romance. Chris Stein knows how to tell a story. Under A Rock is his nothing-spared autobiography. It's about the founding of the band, ascending to the heights of pop success, and the hazards of fortune. Famous names march through these pages-Warhol, Bowie, Jean-Michel Basquiat, and more-but you can get famous names anywhere. What you can't get anywhere else is a plunge into the moments that made a giant 1980's artistic sensation. Stein takes us there in this revelatory, propulsive, distinctive memoir."
Includes index
Keywords: Stein, Chris -- 1950-; Stein, Chris / 1950-; Harry, Debbie; Blondie (Musical group); Rock musicians / United States / Biography; Guitarists / United States / Biography; Autobiographies; Autobiografie